Mechanical earth model coupled with critical drawdown pressure to mitigate sand production in the Nahr Umr Formation, Southern Iraq - Ayal, Ali Mahmoud; Sadeq, Dhifaf Jaafar; Alakbari, Fahd Saeed (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Sand production is one of the major challenges in the oil and gas industry. This problem exists when sand is produced along with oil and gas causing relevant damage to production equipment, thus decreasing in the productivity of wells. Therefore, a comprehensive geomechanical analysis is necessary to mitigate sand production. This study aims to assess the potential of sand production across the Nahr Umr Formation using the 1-D Mechanical Earth Model (MEM). Tech-log software coupled with well log and core data have been employed to accurately determine the possible rock geomechanical parameters, in-situ stresses and pore pressure at which rock failure might occur. Once MEM is complete, the Poro-elastic method is used to figure out the critical drawdown pressure (CDDP) and accurately predict the sand production onset. Additionally, the effect of different well completion types on the value of the CDDP was examined, and thus it was concluded that cased hole completion is the first line of defense against sand production, and can also be considered as a strategy of sand control because it reduces the sand production potential and increases the operation drawdown. Furthermore, to demonstrate the effectiveness and applicability of our method and technique, a case study was conducted to illustrate the reliability of our method in predicting sand-producing intervals under different depletion rates and completion scenarios. The finding showed that the depth 2527.7 m is a potential location for sand production as the CDDP reads a positive value revealing a high potential for rock failure. Moreover, sensitivity analysis has been performed by considering different ranges of Unconfined Compressive Strength (USC), Poisson ratio, minimum horizontal stress (Shmin), maximum horizontal stress (SHmax), vertical stress, sand grain size, perforation diameter, perforation orientations, stress ratio, and hole deviation. These factors play an essential role in optimal decisions related to real-time sand control techniques. Through the results, it is clear that as the UCS, Shmin, and SHmax increase, the sand-free drawdown and depletion also increase, and vice versa. Also, results show that as the depletion rate increases, the CDDP decreases in both cased and open hole conditions, revealing that the onset sanding likely occurs as the depletion rate is elevated. Based on these findings, a necessary modification to the completion design has been made, ensuring sand-free production from a clastic reservoir located in the southern area of Iraq.